Sistem Komunikasi Organisasi Pendidikan - Awaluddinsyah Siregar; Miftah Royyani; Sri Wahyuni (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Organization and communication are two things that cannot be separated, where one is related to the other. Organization is the art of organizing something, while communication is a means of conveying the intentions of the organization. Presumably the ability of school/madrasah principals needs to pay attention to these two aspects so that as leaders, managers (madrasah heads) are able to lead Islamic educational institutions to become superior educational institutions. This type of research uses qualitative research methods, namely research methods used to examine natural objects as experiments. The results of this study indicate that communication is a process of exchanging ideas, messages and contacts, as well as social interaction, including the main activities in human life. Etymologically, the term communication comes from the Latin word communication which is derived from the word communis which means making togetherness or building togetherness between two or more people. Communication in educational organizations can take place at any time involving people who are in the organization, both superiors, subordinates or elements of leadership and subordinates, between teachers and students at school, as well as between students and other students, as well as between teachers and parents. students and so on. Keywords: Communication, Organization, Education